Female leadership influences banks environmental performance - Apsta, Widya; Nur Rahman, Arif (Analisis Data Innovation, 2024)
Purpose – The aim of the study is to analyze the relationship between gender diversity in corporate leadership and bank environmental performance, particularly in terms of female participation at the level of boards and in executive positions.Design/methodology/approach – Further robustness tests are performed using fixed effects, GLS and system GMM estimations. Regional comparisons are also made to examine differences in impact across different economic contexts.Findings – Our main finding is that increased gender diversity in bank leadership positively affects bank environmental performance. These results suggest adding women to the management team and board enhances the effectiveness of corporate sustainability initiatives, particularly when those initiatives can be supported by CSR committees and a strong governance structure. This effect is stronger in high-income countries where regulatory frameworks and institutionalized support encouraged this response. The conclusions underscore the relevance of gender diversity as a strategic driver of sustainable banking practic.Originality/value – This study fills a gap in the literature regarding the influence of gender diversity on corporate sustainability in the banking sector by providing evidence from the banking context. It also provides a new comparative perspective on the contextual factors of how economic environments determine the impact of gender-inclusive leadership on environmental performance.Research Implications – The results have practicable implications for regulators and banking organizations striving to enhance environmental performance via inclusion leader approaches. Further research is required to determine pathways through which gender diversity may improve corporate sustainability in sectors outside of the banking industry.